Unsteady dissolution of particle of various shapes in a stagnant liquid. (17th February 2015) - Tseng, Shiojenn; Lin, Tzu-Huei; Hsu, Jyh-Ping
Abstract: The dissolution of planar, cylindrical, and spherical particles in a stagnant liquid is analyzed theoretically. Assuming that the diffusion of solute molecules is the rate-determining step, the temporal variation in the particle size is derived. The transient nature of the phenomenon under consideration is taken account of by solving a moving boundary problem through regular perturbation, and a perturbation parameter assessing if the pseudo-steady state assumption made in previous analyses is proposed. The applicability of the analytical result derived is verified by fitting it to the experimental data in the literature. We show that neglecting that transient nature may yield appreciable qualitative and quantitative deviations, especially if a particle has a high solubility, large molecular weight, or low density. Graphical abstract: Highlights: A general diffusion-controlled dissolution model is studied Three representative types of particle are considered A parameter for assessing pseudo-steady state assumption is proposed The model proposed is verified by the experimental data in the literature